Proposed digital marketing strategy: A case of multinational mask producer in indonesia - Amalia, Zahrina (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Triple Nexguard Indonesia, as one of the multinational mask manufacturers in Indonesia, is looking for a large market growth opportunity from this condition. On the other hand, there are several challenges faced by Triple Nexguard Indonesia in dealing with black swan conditions and intense competition, such as product allocation and priority from global market supply, inability to produce locally with acceptable time-to-market. From the research, it is concluded that Triple Nexguard is positioned as the highest protective mask that provides quality assurance with advanced quality screening and strong brand equity with international medical organization patents, with the main target market of people who are very worried and worried about their masks. behavior of the wearer during a pandemic situation. According to this research, the Triple Nexguard Indonesia digital marketing strategy project stream is divided into two major activities that can be carried out in parallel. The first activity is a content marketing strategy that emphasizes strengthening product information content to build brand awareness. Then, the e-commerce strategy focuses on transactional processes. Both strategies stem from consumer behavior that can influence customer paths and journeys.